Message from the Editor-in-Chief: Introducing the Canadian Journal of Wound, Ostomy and Continence (CJWOC) - Martins, Lina (Canadian Journal of Wound, Ostomy and Continence, 2025)
We are thrilled to announce the launch of our newly branded journal, the Canadian Journal of Wound, Ostomy and Continence (CJWOC). Starting with its Spring 2025 Issue, the CJWOC will serve as the official publication of Nurses Specialized in Wound, Ostomy, and Continence Canada (NSWOCC). This exciting transformation marks a significant milestone in our ongoing commitment to excellence, replacing the NSWOC Advance with a more scientific and academically focused journal. The peer-reviewed CJWOC aims to maintain the highest standards of our wound, ostomy, and continence specialty in Canada, providing a platform for cutting-edge research, critical insights, and innovative practices. The Canadian Pressure Injury Advisory Panel (CPIAP) and the International Skin Tear Advisory Panel (ISTAP) are official interest groups of this new publication. The journal is published three times per year—in Spring, Fall, and Winter—and is available in both digital and print formats. It is an open-access, peer-reviewed journal with no article processing fees for authors. We are enthusiastic about this new direction and are dedicated to ensuring that the CJWOC becomes a cornerstone in the field. We invite you to join us in celebrating this evolution and look forward to your contributions to our journal. Together, we will continue to advance the knowledge and practice of wound, ostomy, and continence care in Canada, reflecting the dedication and expertise of our specialized nurses. Stay tuned for more updates and prepare to explore the wealth of information and research that the CJWOC will bring to our community.